Affordances after spinal cord injury. Issue 2 (16th February 2018) - Sedda, Anna; Ambrosini, Ettore; Dirupo, Giada; Tonin, Diana; Valsecchi, Laura; Redaelli, Tiziana; Spinelli, Michele; Costantini, Marcello; Bottini, Gabriella
Abstract : Spinal cord injury can cause cognitive impairments even when no cerebral lesion is appreciable. As patients are forced to explore the environment in a non‐canonical position (i.e., seated on a wheelchair), a modified relation with space can explain motor‐related cognitive differences compared to non‐injured individuals. Peripersonal space is encoded in motor terms, that is, in relation to the representation of action abilities and is strictly related to the affordance of reachability. In turn, affordances, the action possibilities suggested by relevant properties of the environment, are related to the perceiver's peripersonal space and motor abilities. One might suppose that these motor‐related cognitive abilities are compromised when an individual loses the ability to move. We shed light on this issue in 10 patients with paraplegia and 20 matched controls. All have been administered an affordances‐related reachability judgement task adapted from Costantini, Ambrosini, Tieri, Sinigaglia, and Committeri (2010, Experimental Brain Research, 207, 95) and neuropsychological tests. Our findings demonstrate that patients and controls show the same level of accuracy in estimating the location of their peripersonal space boundaries, but only controls show the typical overestimation of reaching range. Secondly, patients show a higher variability in their judgements than controls. Importantly, this finding is related to the patients' ability to perform everyday tasks. Finally, patients are not faster in making their judgements on reachability in peripersonal space, while controls are. Our results suggest that not moving freely or as usual in the environment impact decoding of action‐related properties even when the upper limbs are not compromised.